A framework on information and communication technology (ICT) implementation issues: a case study on the local governments of Selangor, Malaysia / Rugayah Hashim - Hashim, Rugayah (2008)
The purpose of this research was to identify the issues that hinder the successful implementation of information and communication technologies (ICT) in the local governments of Selangor, Malaysia and, construct a framework of these issues. Mixed methodologies were employed where the quantitative analysis provided the foundation to corroborate and triangulate the discoveries from the qualitative analyses of the interviews, observations, field notes and documents conducted and obtained from the cases identified. Theoretical sampling technique was applied to determine the respondents where, an unstructured interview guide was used to probe and gather rich, in-depth data. The rigorous analyses of data allowed for the emergence of issues which were appropriately grouped into relevant themes. These themes provided the basis for the formation of a framework on ICT project implementation. The findings showed that four prominent themes validate both analyses, and these are social, technological, economic and political issues. Aside from these four main themes, the specific sub-issues formed the indicators for ICT implementation failures in the Selangor local governments. Each of these sub-issues is integral to developing a comprehensive understanding of the problems associated with ICT implementation in order to optimize the cost, time and value of investments in ICT. The emergent themes provided the groundwork for future deployment of ICT policies and strategies to the policymakers and ICT stakeholders. Further research is recommended to cascade down the themes into ICT key performance indicators and initiatives, so that the objectives of accomplishing the national ICT mission and vision are also met.